University of Puerto Rico - School of Pharmacy: One Hundred Years of History and Service - Maldonado-Dávila, Wanda T. (Puerto Rico Health Sciences Journal, 2013)
The University of Puerto Rico School of Pharmacy was initially established as the Department of Pharmacy at the Río Piedras Campus on September 22, 1913, being the first healthcare program founded in Puerto Rico. The history of the School of Pharmacy reveals a remarkable evolution over a 100 years period in order to respond to the patients’ and societal needs. The programs offered by the school have adapted to the wealth of scientific knowledge, emerging technologies, patients’ needs and changes in the healthcare system. This historical note highlights the most important milestones of this centennial institution.